2017
DOI: 10.3126/nje.v7i1.17757
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variations in Perception of Human Papillomavirus and its Vaccination among Young Women in Nepal

Abstract: Background: The Human Papillomavirus (HPV) is strongly associated with cervical and other cancers. In women, cervical cancer is the third most common cancer. HPV infection can be largely prevented through vaccination of (adolescent) girls. At the same time, Nepal is a low-income country experiencing a cultural change in attitudes towards sex and sexual behaviour. However, in the adolescent population knowledge about HPV, factors associated with an increased risk of HPV and the existence of the vaccination is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…[75][76][77] In some cultures, women also need approval from their husband to vaccinate their child against HPV. 75,76,78 In the event that the 9-valent HPV vaccine comes to be recommended for women who have initiated sexual behavior, it is important to gain male opinion about their partner being vaccinated against the sexually transmitted HPV infection and to determine whether or not men would support their partner seeking HPV vaccination. Married women in most Asian sociocultural contexts will seek their husband's permission regarding their own healthcare before making a decision.…”
Section: Gender Roles In Decision-makingmentioning
confidence: 99%
“…[75][76][77] In some cultures, women also need approval from their husband to vaccinate their child against HPV. 75,76,78 In the event that the 9-valent HPV vaccine comes to be recommended for women who have initiated sexual behavior, it is important to gain male opinion about their partner being vaccinated against the sexually transmitted HPV infection and to determine whether or not men would support their partner seeking HPV vaccination. Married women in most Asian sociocultural contexts will seek their husband's permission regarding their own healthcare before making a decision.…”
Section: Gender Roles In Decision-makingmentioning
confidence: 99%
“…En otros trabajos sí se ha hallado asociación entre el VPH y estos factores (23)(24)(25)(26)(27)(28)(29) . Sathian y col. y Bosch y col. mencionan que la promiscuidad y el número de parejas sexuales son factores de infección por el VPH (30,31) y el estudio de Francheschi y col. menciona que existe relación entre la infección por VPH y la edad de primera relación sexual (32) .…”
Section: Discussionunclassified
“…All the studies were conducted in university settings among college students except one which was conducted in the community setting with undergraduate college students. They conducted a face-to-face interview for the data collection process (Sathian et al, 2017). Five studies used a paper-based self-administered questionnaire to collect the data (Koc, 2015;Rashid et al, 2016;Kasymova et al, 2018;Farazi et al, 2018;Kamimura et al, 2018).…”
Section: Methodology Of Previous Studiesmentioning
confidence: 99%
“…In a study conducted in Cyprus, the majority (91%) of the students reported that they had heard about HPV (Farazi et al, 2018). The findings from the study conducted among the female college students in Nepal revealed that 71.7% of the participants had the knowledge about HPV however, only 51.8% of the students knew about the HPV vaccine (Sathian et al, 2017). Studies conducted in the US have found moderate to higher HPV and HPV vaccine awareness level whereas studies conducted outside the US showed low HPV and HPV vaccine awareness level (Barnard et al, 2017;Kasymova et al, 2018;Cooper et al, 2018;Koc, 2015;Sathian et al, 2017).…”
Section: Hpv and Hpv Vaccine Awarenessmentioning
confidence: 99%